Silica-aluminum cementing material proportion design method and application thereof
By adjusting the ratio of silicon-aluminum gelling materials, the problems of excessive amount of exciter and fluctuations in the existing technology are solved according to the ionic dissolution characteristics of the raw materials and the use of exciters, and the efficient and accurate silicon-aluminum gelling materials are achieved, thereby improving the performance and engineering reliability of the material.
Patent Information
- Application Number
- CN202411527459.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-25
AI Technical Summary
In the preparation of silicon-aluminum gelling materials, the prior art requires a large amount of strong alkali excitation and high temperature maintenance, resulting in excessive amounts of excitant, alkali evolution and durability problems, and performance differences and fluctuations are large, making it difficult to quickly determine the optimal ratio.
By combining the depolymerization-polycondensation reaction mechanism of silicon-aluminum gelling materials, the ratio of silicon-aluminum gelling materials is adjusted according to the ionic dissolution characteristics of different raw materials, and the ionic dissolution is mixed with the precursor for ionic dissolution. The priority is judged based on the optimal ionic dissolution rate to determine the optimal ratio.
It has achieved rapid determination of the optimal ratio of silicon-aluminum gelling materials, reduced the amount of exciter, improved the strength, durability and chemical corrosion resistance of the material, and ensured that the performance meets the expected standards.
Smart Images

Figure CN119517239A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon-aluminum gelling materials, and in particular relates to a silicon-aluminum gelling material ratio design method and application thereof. Background Art
[0002] In recent years, aluminosilicate cementitious materials have attracted much attention because their precursors are mainly industrial solid waste containing aluminosilicate glass and they have excellent mechanical properties. Aluminosilicate cementitious materials can not only reduce the consumption of cement clinker in the building materials industry, but also absorb solid waste. Therefore, the production and preparation of aluminosilicate cementitious materials can effectively promote the realization of my country's green resource recycling goals and help the healthy and sustainable development of the cement and waste-producing industries.
[0003] At present, the preparation research of silica-alumina gelling materials is flourishing. A large number of scholars use fly ash, metakaolin, steel slag, Bayer red mud, sintering red mud, etc. as precursors, relying on existing experience and data, and determine the best ratio through repeated experiments. Although the above method can obtain the silica-alumina gelling material ratio that meets the target performance, according to the preparation method disclosed in the prior art, in order to make the obtained silica-alumina gelling material have better strength and other properties, a large amount of strong alkali is usually used for excitation, and the curing temperature is increased, so as to promote the depolymerization and repolymerization reaction of the low-activity amorphous phase material. However, the actual amount of the activator far exceeds the demand for the excited solid waste, which leads to the problems of alkali precipitation and durability of the silica-alumina gelling material. In addition, according to the preparation method disclosed in the prior art, the type of solid waste, the selection and dosage of the activator type, the chemical composition and activity of the same type of different source silicate precursors will all bring about performance differences and fluctuations of the silica-alumina gelling materials. In order to obtain the best ratio, a large number of experimental studies are required.
[0004] Based on the above, the silica-alumina cementitious materials industry urgently needs a design and research method for preparing silica-alumina cementitious materials using solid waste as precursors, quickly determining the optimal ratio of solid waste materials, reducing or even avoiding the actual amount of activator far exceeding the demand for the activated solid waste, and making the prepared cementitious materials have the best performance. Summary of the invention
[0005] During the research process, the inventors discovered that by combining the depolymerization-condensation reaction mechanism of silica-alumina gelling materials (i.e., under alkaline conditions, the silicon-oxygen bonds and aluminum-oxygen bonds in silica-alumina solid waste are broken, and silicon, aluminum monomers and calcium ions are released (if it is a high-calcium raw material) and dissolved; when the concentration of calcium, silicon, aluminum and other ions in the gelling material slurry reaches a critical value, a polymerization reaction occurs to form a gel and provide strength), and adjusting the silica-alumina gelling material ratio according to the ion dissolution characteristics of different raw materials, not only can waste and by-products be effectively utilized, resource waste and carbon emissions can be reduced, and green and sustainable development can be promoted; its strength, durability and chemical corrosion resistance can also be enhanced, ensuring that the prepared silica-alumina gelling materials can meet the expected performance standards in practical applications.
[0006] In view of this, the main purpose of the present invention is to provide a method for designing the proportion of silica-alumina gelling materials and its application based on the dissolution characteristics of raw materials; the technical problem to be solved is how to provide a method for designing the proportion of silica-alumina gelling materials so that it can quickly determine the optimal formula for preparing silica-alumina gelling materials from different precursors under the action of an activator.
[0007] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the present invention, a method for designing the proportion of a silicon-aluminum gelling material and its application, wherein the method comprises the following steps:
[0008] The precursor and the activator solution are mixed in different proportions for ion dissolution; the optimal ion dissolution rate judgment rule is as follows: the dissolution amount of silicon ions is X, the dissolution amount of aluminum ions is Y, and the dissolution amount of calcium ions is Z; the sum of aX and Y is the largest, and Y:X is 0.10-0.50:1; bX and Y have the largest ratio; cZ has the largest value; the priority of the optimal ion dissolution rate judgment is a>b>c;
[0009] The proportion of silica-alumina gelling material is determined according to the optimal dissolution rate of ions.
[0010] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0011] Preferably, in the aforementioned design method, the precursor is industrial solid waste.
[0012] Preferably, in the aforementioned design method, the industrial solid waste is any one or more of kaolin, red mud, mineral powder, steel slag, lithium slag, gypsum, coal gangue, fly ash, coal cinder, and blast furnace slag.
[0013] Preferably, in the aforementioned design method, the activator is at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate, and potassium sulfate.
[0014] Preferably, in the aforementioned design method, the Y:X is 0.15-0.35:1.
[0015] Preferably, in the aforementioned design method, when the precursor contains two kinds of industrial solid wastes, the precursor is prepared by mixing them with the activator solution in proportions of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 respectively.
[0016] Preferably, in the aforementioned design method, when the precursor contains three types of industrial solid wastes, the precursor is prepared by mixing them with the activator solution in ratios of 6:2:2, 2:6:2, 2:2:6, 1:4.5:4.5, 1:2:7, and 1:7:2 respectively.
[0017] Preferably, in the aforementioned design method, during the mixing process of the precursor and the activator solution, the mass ratio of the activator to the precursor is 1.0%, 3.0%, 5.0%, 7.0%, or 9.0% based on solid content.
[0018] Preferably, the aforementioned design method further comprises the following steps:
[0019] After the precursor and activator solutions are mixed, the resulting mixture is cooled to room temperature before ion dissolution begins.
[0020] Preferably, in the aforementioned design method, the dissolution test temperature for ion dissolution is 20-25°C and the dissolution time is 60-80 min.
[0021] Preferably, the aforementioned design method further comprises the following steps: during the ion dissolution process, the mixed solution is stirred at a stirring speed of 800 to 1200 rpm.
[0022] The purpose of the present invention and the technical problem solved by the present invention are also achieved by the following technical solutions. According to the present invention, a silicon-aluminum cementitious material is provided, wherein the mortar formed by the present invention has a flexural strength of >6.0MP and a compressive strength of >40.0MP after curing in water for 3 days; and a flexural strength of >7.0MP and a compressive strength of >41.0MP after curing in water for 28 days.
[0023] The purpose of the present invention and the technical problem solved are also achieved by the following technical solutions: The aforementioned silicon-aluminum gelling material is used in the fields of building decoration, road traffic engineering, building foundation, floor or roofing materials.
[0024] By means of the above technical solution, the method for designing the proportion of silicon-aluminum gelling materials and its application proposed by the present invention have at least the following advantages:
[0025] 1. The present invention proposes a method for designing the proportion of aluminosilicate gelling materials and its application. Based on the dissolution characteristics of raw materials, the reaction and dissolution behavior of silicon and aluminum of aluminosilicate precursors in activator solutions is systematically analyzed, and the mechanical properties are used as evaluation criteria, and the optimal proportion of raw materials is determined by the amount of ion dissolution. Compared with traditional design methods (such as orthogonal test methods), the steps of preparing aluminosilicate gelling materials, curing them, and testing their properties to further screen out the best aluminosilicate gelling materials to determine the best formula are omitted, thereby saving related input production costs and time costs. Therefore, the method for designing the proportion of aluminosilicate gelling materials proposed in the present invention has the advantages of high efficiency, accuracy, reduced resource waste, and improved engineering reliability.
[0026] 2. The ratio design method of the silicon-aluminum gelling material proposed in the present invention and its application can also flexibly adjust the ratio of different raw materials in the precursor according to the richness of silicon, aluminum and calcium contained in the raw materials by analyzing the ion dissolution, so as to optimize the formula and make the prepared silicon-aluminum gelling material have better performance. Therefore, the ratio design method of the silicon-aluminum gelling material proposed in the present invention also has the advantages of flexibility, customization, and environmental friendliness.
[0027] 3. The present invention proposes a method for designing the proportion of alumina-silica gelling materials and its application, which can detect the ions dissolved by the precursor under the action of the activator, and then determine whether the activator is used excessively, thereby avoiding the degradation of the performance of the alumina-silica gelling materials due to excessive activator, so that the performance of the prepared alumina-silica gelling materials is guaranteed, and the appropriate use of the activator is also conducive to cost saving.
[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Example 1 Ion dissolution rate curve of red mud and mineral powder at different dosages of the optimal activator;
[0030] Figure 2 Example 3: Curve diagram showing the effect of the mass ratio of red mud to mineral powder on the dissolution of Si, Al and Ca ions in the red mud-mineral powder binary system. DETAILED DESCRIPTION
[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a method for designing the proportion of a silicon-aluminum gelling material and its application proposed by the present invention in combination with the accompanying drawings and preferred embodiments. Its specific implementation method, structure, characteristics and effects are described in detail as follows.
[0032] A method for designing the proportion of a silicon-alumina gelling material according to the present invention comprises the following steps:
[0033] The precursor and the activator solution are mixed in different proportions for ion dissolution; the precursor of the present invention refers to a raw material that can produce silicon ions, aluminum ions and calcium ions under the action of the activator to form a silicon-aluminum gelling material. The precursor can be industrial solid waste, and the industrial solid waste is any one or more of metakaolin, red mud, mineral powder, steel slag, lithium slag, gypsum, coal gangue, fly ash, coal slag, and blast furnace slag. The present invention uses industrial solid waste as a raw material to prepare silicon-aluminum gelling materials, which is conducive to environmental protection and saving investment costs. Preferably, in some embodiments, more than two kinds of industrial solid wastes are selected to mix to prepare silicon-aluminum gelling materials. This is because the mixing of different minerals and the doping of chemical components can better activate the bonding force between ions, reduce the difficulty of ion depolymerization, and promote the dissolution of ions in the system. Therefore, the precursor contains different industrial solid wastes, which has an important influence on the reaction activity and reaction degree of its reaction system. This point is demonstrated by the present invention through specific embodiments.
[0034] The activator can be an alkaline activator or an acidic activator; preferably, the alkaline activator or the acidic activator is a weak acid or a weak base. Selecting a weak acid or a weak acid as the activator is more conducive to the silicon, aluminum and calcium dissolved from the precursor under the action of the activator to exist in the form of ions, which is conducive to ensuring that the formed silicon-aluminum gel material has good performance. In some embodiments, the activator used in the present invention is at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate and potassium sulfate.
[0035] In order to better determine the ratio of different raw materials in the precursor and the amount of the activator added to the precursor by dissolution test, the present invention reasonably designs the ratio of different raw materials in the precursor and the ratio of the amount of the activator (in terms of solid content) to the total mass of the precursor in the process of determining the ratio design of the silicon-alumina gelling material based on the dissolution characteristics of the raw materials, as follows:
[0036] In some embodiments, when the precursor contains two types of industrial solid waste, the precursors are prepared in ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, respectively.
[0037] In other embodiments, when the precursor contains three types of industrial solid waste, the precursors are prepared according to the ratios of 6:2:2, 2:6:2, 2:2:6, 1:4.5:4.5, 1:2:7, and 1:7:2, respectively.
[0038] In other embodiments, during the mixing process of the precursor and the activator solution, the amount of the activator solution added, calculated on a solid content basis, is 1.0%, 3.0%, 5.0%, 7.0%, or 9.0% by mass to the precursor.
[0039] In addition, in order to make the precursor more easily and completely excited by the activator, the present invention also pre-treats the precursor, specifically as follows:
[0040] a. Homogenize and dry the different raw materials of the precursor respectively;
[0041] b. Grinding: Grind the precursor raw materials treated in step a separately until they are ground into powders with a sieve residue of no more than 10% when passing through an 80 μm square hole sieve; mix the powders before and after sieving to form a grinding body.
[0042] The present invention mixes the precursor grinding body formed after pretreatment with the activator in proportion. Since heat is released during the mixing process of the precursor and the activator, in order to avoid the influence of temperature change on the ion dissolution rate, the mixed solution needs to be cooled to room temperature. In some embodiments, the room temperature is 20-25°C.
[0043] The present invention starts to conduct a dissolution test on the cooled activator and precursor mixed solution, and strictly controls various process parameters of the dissolution test so that the precursor can dissolve silicon ions, aluminum ions, and calcium ions as much as possible under the action of the activator, and exist in the form of ions. In some embodiments, the temperature of the dissolution test is 20-25°C; the dissolution time is 60-80 minutes.
[0044] In addition, in order to allow the activator to fully contact the precursor and dissociate the polymer in the precursor and dissolve it in the form of ions as much as possible, the present invention stirs the mixed solution formed by mixing the activator solution and the precursor at a stirring speed of 800-1200 rpm.
[0045] After the ion dissolution test of the present invention is completed, the optimal ion dissolution rate is determined as follows: the dissolution amount of silicon ions is X, the dissolution amount of aluminum ions is Y, and the dissolution amount of calcium ions is Z.
[0046] The sum of aX and Y is the largest, and Y:X is 0.10~0.50:1.
[0047] When the amount of silicon and aluminum ions dissolved is the largest, it reflects that the raw materials of this group of precursors have a large dissolution rate under the action of the activator, and the dissolution is more complete, which is more conducive to the polymerization reaction (polymerization reaction is the breaking and reorganization of the -Si-O-Si- or -Si-O-Al- bonds of the silicate, forming a silicate aluminum-based polymer with a new amorphous three-dimensional network structure). Since the material structure formed by the polymerization reaction has a decisive influence on the strength of the material, the final strength is the highest.
[0048] The silicon-aluminum ratio will directly affect the formation and microstructure of hydration products. The specific reasons are as follows:
[0049] 1. When the silicon-aluminum ratio is low, the silicate chain is shorter, and more short-chain gel products may be formed. These short-chain gel products are easier to overlap with each other to form a network structure, but may lead to relatively low strength of the overall structure;
[0050] 2. When the silicon-aluminum ratio is high, the silicate chains may be longer, forming a more complex network structure, which usually has higher strength because the interaction between the silicate chains is stronger and can more effectively resist external loads. However, as the silicon-aluminum ratio continues to increase, the compressive strength of the alkali-activated cementitious material usually shows a trend of first increasing and then stabilizing. Therefore, the present invention strictly controls the silicon-aluminum ratio within a certain range so that the compressive strength of the material meets the preset requirements. This is because under this condition, the interaction between the silicate chains and the aluminate chains is strong, forming a dense network structure.
[0051] bThe ratio of X to Y is the largest;
[0052] When the precursor and the activator are mixed in different proportions, the sum of the dissolved ion contents X and Y is consistent, and the Y:X ratio is in the range of 0.10 to 0.50:1; further comparing the ratio of X to Y, when the ratio of X to Y is the largest, it is determined to be the best ion dissolution. This is because the interaction between the silicate chain and the aluminate chain is the strongest at this time, forming the most dense network structure.
[0053] cZ value is the largest;
[0054] When the precursor and the activator are mixed in different proportions, the sum of the dissolved ion contents X and Y is consistent, and the Y:X ratio is in the range of 0.10-0.50:1, and the ratio of X to Y is consistent, further judgment is made based on the content of calcium ions in the dissolved ions. If the calcium ion content is the highest, it is determined to be the best ion dissolution. The reason is that the higher the calcium ion content, the higher the dissolution rate of the precursor raw material ions, and the higher the strength of the formed silica-alumina gelled material.
[0055] In summary, after the ion dissolution test is completed, the priority of the optimal dissolution rate of the dissolved ions is judged as a>b>c; and the optimal ratio of the silicon-aluminum gelling material is determined according to the optimal dissolution rate of the ions.
[0056] Preferably, in the aforementioned optimal ion dissolution rate judgment rule, the Y:X ratio in step a is 0.15-0.35:1; under this condition, the formed silica-alumina gelled material has excellent strength.
[0057] The present invention also uses the best raw material dissolution characteristics to determine the best raw material ratio for preparing the silica-alumina gel material, uses the screened best ratio as a formula, and then prepares the silica-alumina gel material and tests its performance, such as bending resistance and compression resistance. The present invention also designs an orthogonal test by using the same precursor and activator type, and tests and screens the performance of the best silica-alumina gel material prepared by the orthogonal test, and compares it with the performance of the silica-alumina gel material prepared by the present invention using the formula determined based on the best raw material dissolution characteristics. The results show that the performance of the two is basically the same. This shows that the design method proposed by the present invention for determining the best ratio for preparing the silica-alumina gel material based on the best raw material dissolution characteristics is feasible. Moreover, compared with the traditional orthogonal experiment method, the ratio design method of the silica-alumina cementitious material proposed in the present invention is time-saving, efficient and cost-saving; further, the design method of the present invention can also objectively and accurately determine whether the dosage of the activator is excessive, thereby avoiding the problems of excessive gel material caused by excessive activator, resulting in reduced strength, reduced durability, increased shrinkage and poor working performance of the silica-alumina cementitious material, thereby ensuring that the prepared silica-alumina cementitious material has good performance.
[0058] Based on the above, the method for designing the proportion of a silicon-aluminum gelling material proposed by the present invention has application value and economic value in the field of preparing silicon-aluminum gelling material by mixing a precursor and an activator.
[0059] The present invention prepares the silica-alumina cementitious material according to the optimal formula determined based on the optimal raw material dissolution characteristics. The mortar formed by the present invention has a flexural strength of >6.0MP and a compressive strength of >40.0MP after curing in water for 3 days; and a flexural strength of >7.0MP and a compressive strength of >41.0MP after curing in water for 28 days.
[0060] The present invention also proposes that the silicon-aluminum gelling material prepared by the above method can be used in the fields of building decoration, road traffic engineering, building foundation, floor or roofing materials, etc.
[0061] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0062] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0063] The embodiment of the present invention discloses a method for designing and determining the optimal ratio of raw materials for preparing a silicon-aluminum gel material by using an ion dissolution test and its application. (All the activators below are of analytical grade).
[0064] Example 1 Determination of the best activator for preparing silicon-alumina gelling material using red mud and mineral powder as raw materials
[0065] In this embodiment, different activators are mixed with red mud and mineral powder and ion dissolution test is carried out to determine the best activator. The specific method is as follows:
[0066] 1) Precursor preparation
[0067] a. Raw material pretreatment: homogenize and dry red mud and mineral powder respectively;
[0068] b. Grinding: Grinding the red mud treated in step a until it becomes a powder having a sieve residue of no more than 10% when passing through an 80 μm square hole sieve; mixing the powder before and after sieving to form a red mud grinding body; processing the mineral powder treated in step a according to the pretreatment method of the red mud grinding body to obtain a mineral powder grinding body;
[0069] c. Ingredients: fully mix the red mud ground body and the mineral powder ground body in a ratio of 1:1 to prepare a silicon-alumina gelling material precursor with a total mass of 450g.
[0070] 2) Preparation of stimulant
[0071] Activator 1: Sodium hydroxide
[0072] According to the total mass of the precursor, sodium hydroxide was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in turn to form sodium hydroxide solutions of a series of concentrations.
[0073] Activator 2 Sodium carbonate
[0074] According to the total mass of the precursor, sodium carbonate was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in turn to form sodium carbonate solutions of a series of concentrations.
[0075] Activator 3 Potassium Sulfate
[0076] According to the total mass of the precursor, potassium sulfate was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in turn to form potassium sulfate solutions of a series of concentrations.
[0077] 3) Precursor and activator mixing
[0078] According to the solid-liquid ratio of 1:100 (g / mL), 100mL of the prepared activator solution is measured and mixed with 1.000g of the precursor. Different activators are mixed with the prepared precursors according to the above ratio and placed in a conical flask, and a magnetic stirrer is added to each, and the conical flask is sealed. After the solution cools to room temperature (20℃), the dissolution test is started.
[0079] 4) Ion dissolution test
[0080] Preset dissolution test conditions: dissolution test temperature is 20°C, and dissolution time is 60 minutes.
[0081] After the temperature of the constant temperature water bath reaches the preset temperature condition, the sealed conical flask is placed in the constant temperature water bath, the magnetic stirrer continuously stirs the mixture at a speed of 1000 rpm, and the ion dissolution is started according to the preset dissolution test conditions.
[0082] 5) Index detection
[0083] Ion concentration test: The conical flask that has completed the ion dissolution test was filtered, the filtrate was collected and transferred to a 250mL volumetric flask, and the volume was fixed with deionized water. All filtrate samples were uniformly tested for ion concentration within 24 hours. The results are shown in Table 1.
[0084] According to the dissolution of silicon and aluminum ions in red mud and mineral powder, the best activator is determined, and the ion dissolution rate curve of red mud and mineral powder at different dosages of the best activator is drawn.
[0085] Summary: It can be seen from Table 1 that when sodium carbonate is used as the activator and its dosage is 7.0% of the total mass of the precursor, the dissolution amount of silicon and aluminum ions in the ion dissolution test of red mud and mineral powder is the largest, and the dissolution content ratio of aluminum ions to silicon ions is 0.20, which meets the ratio requirement of aluminum ions to silicon ions in this case. Therefore, it is determined that when red mud and mineral powder are used as raw materials to prepare silicon-aluminum gelling materials, the best activator is sodium carbonate.
[0086] pass Figure 1 It can be seen that the increase in the amount of sodium carbonate can increase the concentration of OH ions in the solution to a certain extent, thereby accelerating the fracture of Si-O, Al-O, and Ca-O, and further accelerating the dissolution of Si, Al, and Ca. However, as the amount of sodium carbonate increased from 1.0wt.% to 9.0wt.%, the dissolution rate of Si ions showed a trend of first increasing and then decreasing. This is because during the ion dissolution process, when the silicon and aluminum content reaches a certain concentration, sodium aluminosilicate and calcium aluminosilicate (N-(C)-ASH) will be generated, thereby consuming part of the dissolved Si and Al ions. The dissolution rate of Ca ions showed a trend of first increasing and then decreasing. On the one hand, this is because the Ca dissolved from the precursor2+ In high alkalinity solutions, it tends to exist in the form of Ca(OH)2; on the other hand, due to the dissolved Ca 2+ Participates in the formation of sodium aluminosilicate and calcium aluminosilicate (N-(C)-ASH) gel products.
[0087] Combined with Table 1 Figure 1 It can be seen that when red mud and mineral powder are used as raw materials and an activator is added, the best activator is sodium carbonate, and the amount of sodium carbonate added is not the more the better. It is necessary to control the amount of sodium carbonate added so that the Si, Al, and Ca dissolved from the red mud and mineral powder exist in ionic state to avoid the formation of sodium aluminosilicate and calcium aluminosilicate (N-(C)-ASH), thereby ensuring that the performance of the final prepared silica-alumina cementitious material is good.
[0088] Example 2 Determination of ion dissolution conditions
[0089] This embodiment uses sodium carbonate as an activator, red mud and mineral powder as raw materials, with a mass ratio of 1:1, and sets different ion dissolution process parameters to determine the ion dissolution conditions. The details are as follows:
[0090] 1) Precursor preparation
[0091] The precursor preparation process parameters and steps of this embodiment are the same as those of embodiment 1.
[0092] 2) Preparation of stimulant
[0093] Based on the total mass of 450 g of the precursor, sodium carbonate was weighed in a mass ratio of 7.0% to the precursor; then the sodium carbonate was dissolved in 225 mL of deionized water in sequence to form sodium carbonate solutions of a series of concentrations.
[0094] 3) Precursor and activator mixing
[0095] The mixture was mixed, sealed and cooled at a solid-liquid ratio of 1:100 (g / mL) using the same process parameters and steps as in Example 1.
[0096] 4) Ion dissolution test
[0097] To set different preset dissolution test conditions:
[0098] Dissolution test condition 1: The dissolution test temperature was 20°C, and the dissolution time was 60 min. The magnetic stirrer continuously stirred the mixed solution at a speed of 800 rpm.
[0099] Dissolution test condition 2: The dissolution test temperature was 25°C, and the dissolution time was 80 min. The magnetic stirrer continuously stirred the mixed solution at a speed of 1200 rpm.
[0100] Dissolution test condition 3: The dissolution test temperature was 22°C, the dissolution time was 70 min, and the mixed solution was continuously stirred by a magnetic stirrer at a speed of 1000 rpm.
[0101] Dissolution test condition 4: the dissolution test temperature is 20°C, the dissolution time is 60 min, and the magnetic stirrer continuously stirs the mixed solution at a speed of 1000 rpm.
[0102] The four dissolution test conditions set above were adopted, and magnetic stirring was performed in a constant temperature water bath at the corresponding stirring speeds, and the ion dissolution test was performed in parallel.
[0103] 5) Index detection
[0104] Ion concentration test: The ion concentration test was completed uniformly using the same method as in Example 1. The results are shown in Table 2.
[0105] Summary: It can be seen from Table 2 that the ion dissolution concentration results obtained under the four groups of dissolution test conditions in this embodiment are basically consistent.
[0106] Example 3 Determination of the optimal raw material ratio of red mud and mineral powder for preparing silicon-alumina gelling material
[0107] This example uses the best activator sodium carbonate determined in Example 1, uses different concentrations of sodium carbonate, adjusts the ratio of red mud to mineral powder to prepare different precursors, mixes the activator with the precursor, and determines the best raw material ratio for preparing the silicon-alumina gelling material based on the ion dissolution results of the red mud and mineral powder under the action of the activator. The specific method is as follows:
[0108] 1) Precursor preparation
[0109] The red mud and mineral powder were pretreated and ground using the method of Example 1.
[0110] Ingredients: The obtained red mud ground body and mineral powder ground body are fully mixed in the following proportions: the mass ratio of the red mud ground body to the mineral powder ground body is 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, 0:10; different silica-alumina gelling material precursors are prepared, and the total mass of each precursor is 450g.
[0111] 2) Preparation of stimulant
[0112] According to the total mass of the precursor, sodium carbonate was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in sequence to form sodium carbonate solutions of a series of concentrations.
[0113] 3) Precursor and activator mixing
[0114] The activator and the precursor were mixed at a solid-liquid ratio of 1:100 (g / mL). Different activators were mixed with different precursors at the above solid-liquid ratio and placed in a conical flask, and a magnetic stirrer was added to each. The conical flask was sealed. After the solution cooled to room temperature (20°C), the dissolution test was started.
[0115] 4) Ion dissolution test
[0116] Preset dissolution test conditions: dissolution test temperature is 20°C, and dissolution time is 60 minutes.
[0117] After the temperature of the constant temperature water bath reaches the preset temperature condition, the sealed conical flask is placed in the constant temperature water bath, the magnetic stirrer continuously stirs the mixture at a speed of 1000 rpm, and the ion dissolution is started according to the preset dissolution test conditions.
[0118] 5) Index detection
[0119] Ion concentration test: The ion dissolution test was carried out using the method of Example 1. The results are shown in Table 3.
[0120] Ion dissolution curve drawing: Draw a curve of the effect of the mass ratio of red mud to mineral powder on the dissolution capacity of Si, Al and Ca in the red mud-mineral powder binary system under the conditions of 20°C and 7.0wt.% sodium carbonate. Figure 2 .
[0121] Summary: It can be seen from Table 3 that when the ratio of red mud to mineral powder is 2:8 and the dosage of the activator sodium carbonate is 7.0% of the total mass of red mud and mineral powder, the dissolution amount of silicon and aluminum ions is the largest, and the dissolution content ratio of aluminum ions to silicon ions is 0.28, which meets the requirements of the ratio range of aluminum ions to silicon ions in this case.
[0122] pass Figure 2 It can be seen that after the combination of red mud and mineral powder, the dissolution amounts of Si, Al and Ca in the system have been increased compared to single-component red mud and mineral powder. Moreover, the total amount of Si, Al and Ca dissolved after the combination of red mud and mineral powder in any proportion is higher than the total amount of Si, Al and Ca dissolved in single-component red mud and mineral powder. This is because the mineral mixing of red mud and mineral powder and the doping of chemical components better activate the bonding force between ions, reduce the difficulty of ion depolymerization, and promote the dissolution of ions in the system. Therefore, the mineral mixing of red mud and mineral powder has an important influence on the reaction activity and reaction degree of its reaction system. Moreover, if Figure 2 As shown, when the mineral powder accounts for 20%, the dissolution amount of silicon ions, calcium ions and the total dissolution amount of the three ions is the largest.
[0123] Therefore, when red mud and mineral powder are used as raw materials to prepare siliceous-aluminous cementitious materials, the optimal raw material ratio is as follows: in terms of mass percentage, the ratio of red mud to mineral powder is 2:8, and the amount of activator sodium carbonate is 7.0% of the total mass of red mud and mineral powder.
[0124] Example 4 Determination of the optimal raw material ratio for preparing silicon-aluminum gelling material using steel slag and lithium slag
[0125] In this example, sodium carbonate is used as an activator, and a method substantially the same as that in Example 3 is used to determine the optimal raw material ratio when steel slag and lithium slag are used as precursors to prepare a silicon-alumina gelled material.
[0126] The specific method is as follows:
[0127] 1) Precursor preparation
[0128] The steel slag and lithium slag are pretreated and ground in the same manner as the method for pretreating and grinding red mud and mineral powder in Example 3.
[0129] Ingredients: The obtained steel slag ground body and lithium slag ground body were mixed in proportions of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 to prepare different silicon-aluminum gelling material precursors, and the total mass of each precursor was 450 g.
[0130] 2) Preparation of stimulant
[0131] According to the total mass of the precursor, sodium carbonate was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in sequence to form sodium carbonate solutions of a series of concentrations.
[0132] 3) Precursor and activator mixing
[0133] The mixture was mixed, sealed and cooled at a solid-liquid ratio of 1:100 (g / mL) using the same process parameters and steps as in Example 3.
[0134] 4) Ion dissolution test
[0135] The ion dissolution was carried out using the same dissolution test process conditions and steps as in Example 3.
[0136] 5) Index detection
[0137] Ion concentration test: The ion dissolution test method of Example 3 was used for testing. The results are shown in Table 3.
[0138] Summary: The present embodiment study shows that when using steel slag and lithium slag as precursors to prepare silicon-alumina gelling materials, the best raw material ratio is as follows: the mass ratio of steel slag to lithium slag is 4:6, and the amount of activator added is 5.0% of the total mass of the precursor.
[0139] Example 5 Determination of the optimal raw material ratio for preparing silicon-aluminum gelling material using steel slag and red mud
[0140] In this example, sodium carbonate is used as an activator, and a method substantially the same as that in Example 3 is used to determine the optimal raw material ratio when steel slag and red mud are used as precursors to prepare a silicon-alumina gelling material.
[0141] The specific method is as follows:
[0142] 1) Precursor preparation
[0143] The steel slag and red mud are pretreated and ground in the same manner as in Example 3.
[0144] Ingredients: The obtained steel slag ground body and red mud ground body were mixed in the proportions of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 to prepare different silicon-aluminum gelling material precursors, and the total mass of each precursor was 450 g.
[0145] 2) Preparation of stimulant
[0146] According to the total mass of the precursor, sodium carbonate was weighed in a ratio of 1.0%, 3.0%, 5.0%, 7.0%, and 9.0% to the total mass of the precursor; and then dissolved in 225 mL of deionized water in sequence to form sodium carbonate solutions of a series of concentrations.
[0147] 3) Precursor and activator mixing
[0148] The mixture was mixed, sealed and cooled at a solid-liquid ratio of 1:100 (g / mL) using the same process parameters and steps as in Example 3.
[0149] 4) Ion dissolution test
[0150] The ion dissolution was carried out using the same dissolution test process conditions and steps as in Example 3.
[0151] 5) Index detection
[0152] Ion concentration test: The ion dissolution test method of Example 3 was used for testing. The results are shown in Table 3.
[0153] Summary: The present embodiment study shows that when red mud and steel slag are used as precursors to prepare silicon-alumina gelling materials, the best raw material ratio is as follows: the mass ratio of red mud to steel slag is 6:4, and the amount of activator added is 9.0% of the total mass of the precursor.
[0154] Example 6 Determination of the optimal raw material ratio for preparing silicon-aluminum gelling material from lithium slag and red mud
[0155] In this example, sodium carbonate is used as an activator, and a method substantially the same as that in Example 3 is used to determine the optimal raw material ratio when lithium slag and red mud are used as precursors to prepare a silicon-alumina gelling material.
[0156] The specific method is as follows:
[0157] 1) Precursor preparation
[0158] The lithium slag and red mud are pretreated and ground in the same manner as the method for pretreating and grinding the red mud and mineral powder in Example 3.
[0159] Ingredients: The obtained lithium slag ground body and red mud ground body were mixed in proportions of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 to prepare different silicon-aluminum gelling material precursors, and the total mass of each precursor was 450 g.
[0160] 2) Preparation of stimulant
[0161] The same series of sodium carbonate solutions with the same concentrations were prepared using the same method as in Example 3.
[0162] 3) Precursor and activator mixing
[0163] The mixture was mixed, sealed and cooled at a solid-liquid ratio of 1:100 (g / mL) using the same process parameters and steps as in Example 3.
[0164] 4) Ion dissolution test
[0165] The ion dissolution was carried out using the same dissolution test process conditions and steps as in Example 3.
[0166] 5) Index detection
[0167] Ion concentration test: The ion dissolution test method of Example 3 was used for testing. The results are shown in Table 3.
[0168] Summary: This example study shows that when red mud and lithium slag are used as precursors to prepare siliceous-aluminous gelling materials, the optimal raw material ratio is as follows: the mass ratio of red mud to lithium slag is 5:5, and the amount of activator added is 7.0% of the total mass of the precursor.
[0169] Example 7 Determination of the optimal raw material ratio for preparing silicon-aluminum gelling material using lithium slag, steel slag and gypsum
[0170] In this example, sodium carbonate is used as an activator, and a method substantially the same as that in Example 3 is used to determine the optimal raw material ratio when lithium slag, steel slag, and gypsum are used as precursors to prepare a silicon-alumina gelling material.
[0171] The specific method is as follows:
[0172] 1) Precursor preparation
[0173] The lithium slag, steel slag and gypsum are pretreated and ground in the same manner as the method for pretreating and grinding the red mud and mineral powder in Example 3.
[0174] Ingredients: The obtained gypsum, lithium slag and steel slag grinding bodies are mixed in the proportions of 6:2:2, 2:6:2, 2:2:6, 1:4.5:4.5, 1:2:7 and 1:7:2 respectively to prepare different silicon-alumina gelling material precursors, and the total mass of each precursor is 450 g.
[0175] 2) Preparation of stimulant
[0176] The same series of sodium carbonate solutions with the same concentrations were prepared using the same method as in Example 3.
[0177] 3) Precursor and activator mixing
[0178] The mixture was mixed, sealed and cooled at a solid-liquid ratio of 1:100 (g / mL) using the same process parameters and steps as in Example 3.
[0179] 4) Ion dissolution test
[0180] The ion dissolution was carried out using the same dissolution test process conditions and steps as in Example 3.
[0181] 5) Index detection
[0182] Ion concentration test: The ion dissolution test method of Example 3 was used for testing. The results are shown in Table 3.
[0183] Summary: The present embodiment study shows that when lithium slag, steel slag and gypsum are used as precursors to prepare silicon-alumina cementitious materials, the best raw material ratio is as follows: in terms of mass percentage, lithium slag: steel slag: gypsum is 7:2:1, and the amount of activator added is 1.0% of the total mass of the precursor.
[0184] Example 8 Preparation of silicon-aluminum gelling material using the optimal ratio determined in Examples 1-7
[0185] This example uses the best raw material ratio determined based on the dissolution characteristics of the raw materials in Examples 1-7 as a formula to prepare a silicon-alumina gelling material. The specific method is as follows:
[0186] Formula 1: In the precursor, the ratio of red mud to mineral powder is 2:8 in terms of mass percentage, and sodium carbonate is used as an activator, and the total mass ratio of sodium carbonate to the precursor is 7.0%.
[0187] Formula 2: In the precursor, the ratio of steel slag to lithium slag is 4:6, calculated by mass percentage, and sodium carbonate is used as an activator, and the total mass ratio of sodium carbonate to the precursor is 5.0%.
[0188] Formula 3: In the precursor, the ratio of red mud to steel slag is 6:4, calculated by mass percentage, and sodium carbonate is used as an activator, and the total mass ratio of sodium carbonate to the precursor is 9.0%.
[0189] Formula 4: In the precursor, the ratio of red mud to lithium slag is 5:5, calculated by mass percentage, and sodium carbonate is used as an activator, and the total mass ratio of sodium carbonate to the precursor is 7.0%.
[0190] Formula 5: In the precursor, the ratio of lithium slag: steel slag: gypsum is 7:2:1 by weight percentage, and sodium carbonate is used as an activator, and the total weight ratio of sodium carbonate to the precursor is 1.0%.
[0191] The above formula is used to mix the activator and the precursor to prepare a silica-alumina cementitious material; then the prepared cementitious material is mixed and formed according to the provisions of GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)", and cured in water: the mortar specimens are demolded after being cured in a curing box at 20℃±2℃ and a relative humidity of not less than 90% for 1 day, and the demolded specimens are placed in water at 20℃±1℃ for curing for 3 days and 28 days.
[0192] Test indicators: According to GB / T 17671-2020 "Test method for strength of cement mortar (ISO method)", the flexural strength and compressive strength of silicon-aluminum cementitious materials made with different formulas are tested. The test method is as follows:
[0193] Mortar specimens with a size of 40 mm × 40 mm × 160 mm were molded at room temperature. After curing in a standard curing box for 24 hours, the specimens were demoulded. Subsequently, they were placed in water at a temperature of 20 ± 2 ° C and continued to cure for 28 days. Three parallel specimens were molded in each group, and the arithmetic mean was taken as the strength data. The results are shown in Table 4.
[0194] The present application further designs comparative examples 1-5, and uses an orthogonal test method to design and study the optimal performance of the prepared silicon-aluminum gelling material when different raw materials are used as precursors.
[0195] Comparative Example 1
[0196] This comparative example adopts the orthogonal test method to design and study the performance of the best silicon-aluminum gelling material prepared with red mud and mineral powder as precursors. The specific method is as follows:
[0197] Precursor preparation: red mud and mineral powder were mixed in mass ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 respectively.
[0198] Activator type: sodium hydroxide, sodium carbonate, potassium sulfate.
[0199] Activator dosage: Calculated on the basis of solid content, the ratio of the activator dosage to the total mass of the precursor is 1.0%, 3.0%, 5.0%, 7.0% and 9.0%.
[0200] Preparation of silica-alumina gelling material: The precursors in the above proportions are mixed with various types of activators respectively, and different activator dosages are used as variables to design and carry out orthogonal experiments to prepare silica-alumina gelling material. The prepared gelling material is mixed and formed according to the same process method and parameters as in Example 8; and the same process parameters and steps as in Example 8 are used for curing.
[0201] Test index: The obtained silicon-aluminum gelling material is tested for bending strength and compressive strength. The test method is the same as that of Example 8; the performance of the best silicon-aluminum gelling material obtained by orthogonal test is recorded. The results are shown in Table 5.
[0202] Comparative Example 2
[0203] This comparative example adopts orthogonal test method to design and study the performance of the best silicon-aluminum gelling material prepared by using steel slag and lithium slag as precursors. The process of this comparative example is basically the same as that of comparative example 1, except that:
[0204] Precursor preparation: Steel slag and lithium slag were mixed in mass ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, respectively.
[0205] The type and dosage of the activator are the same as those in Comparative Example 1; and the method for preparing the silica-alumina gelling material is the same as that in Comparative Example 1.
[0206] Test index: The obtained silicon-aluminum gelling material is tested for bending strength and compressive strength. The test method is the same as that of Example 8; the performance of the best silicon-aluminum gelling material obtained by orthogonal test is recorded. The results are shown in Table 5.
[0207] Comparative Example 3
[0208] This comparative example adopts orthogonal test method to design and study the performance of the best silicon-alumina gelling material prepared with steel slag and red mud as precursors. This comparative example is basically the same as comparative example 1, except that:
[0209] Precursor preparation: Steel slag and red mud were mixed in mass ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, respectively.
[0210] The type and dosage of the activator are the same as those in Comparative Example 1; and the method for preparing the silica-alumina gelling material is the same as that in Comparative Example 1.
[0211] Test index: The obtained silicon-aluminum gelling material was tested for bending strength and compressive strength. The test method was the same as that of Example 8, and the best silicon-aluminum gelling material performance obtained by orthogonal test was recorded. The results are shown in Table 5.
[0212] Comparative Example 4
[0213] This comparative example adopts orthogonal test method to design and study the performance of the best silicon-alumina gelling material prepared with red mud and lithium slag as precursors. This comparative example is basically the same as comparative example 1, except that:
[0214] Precursor preparation: Red mud and lithium slag were mixed in mass ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, respectively.
[0215] The type and dosage of the activator are the same as those in Comparative Example 1; and the method for preparing the silica-alumina gelling material is the same as that in Comparative Example 1.
[0216] Test index: The obtained silicon-aluminum gelling material was tested for bending strength and compressive strength. The test method was the same as that of Example 8, and the best silicon-aluminum gelling material performance obtained by orthogonal test was recorded. The results are shown in Table 5.
[0217] Comparative Example 5
[0218] This comparative example adopts orthogonal test method to design and study the performance of the best silicon-alumina gelling material prepared by using gypsum, lithium slag and steel slag as precursors. This comparative example is basically the same as comparative example 1, except that:
[0219] Precursor preparation: Gypsum, lithium slag and steel slag were mixed in mass ratios of 6:2:2, 2:6:2, 2:2:6, 1:4.5:4.5, 1:2:7 and 1:7:2 respectively.
[0220] The type and dosage of the activator are the same as those in Comparative Example 1; and the method for preparing the silica-alumina gelling material is the same as that in Comparative Example 1.
[0221] Test index: The obtained silicon-aluminum gelling material was tested for bending strength and compressive strength. The test method was the same as that of Example 8, and the best silicon-aluminum gelling material performance obtained by orthogonal test was recorded. The results are shown in Table 5.
[0222] In the following Tables 1 and 3, the amount of the activator added represents the ratio of the mass of the added activator (in terms of solid content) to the total mass of the precursor, in %. The proportion of the solid waste materials in the precursor in Table 3 is in terms of mass percentage.
[0223] Table 1 Ion dissolution results of Example 1
[0224]
[0225] Table 2 Example 2 ion dissolution results
[0226]
[0227] Table 3 Best ion dissolution results and corresponding formulas of Examples 3 to 7
[0228]
[0229] Table 4 Performance of the best silicon-alumina gelling materials prepared by different formulations in Example 8
[0230]
[0231] Table 5 Performance of the best silicon-aluminum gelling materials prepared in Comparative Examples 1-5
[0232]
[0233] Combining the embodiments and comparative examples, it can be seen from Tables 4 and 5 that the silico-alumina gelling material prepared by the formula determined by the design method based on the optimal raw material dissolution characteristics of the present invention has a flexural strength of >6.0MP and a compressive strength of >40.0MP after curing in water for 3 days, and a flexural strength of >7.0MP and a compressive strength of >41.0MP after curing in water for 28 days. In addition, under the same type of precursor and activator, the performance of the silico-alumina gelling material prepared based on the raw material dissolution characteristics is basically consistent with the performance of the optimal silico-alumina gelling material prepared by the orthogonal test method, and the raw material ratio in the precursor of the optimal silico-alumina gelling material and the selection and dosage of the activator are consistent.
[0234] The present invention can be seen from the embodiments and comparative examples that the present invention adopts a design method for determining the optimal ratio of raw materials for preparing silicon-aluminum gelling materials based on the optimal raw material dissolution characteristics, which is consistent with the performance of the optimal silicon-aluminum gelling materials finally obtained by the traditional orthogonal test method. Therefore, the design method for determining the optimal ratio of raw materials for preparing silicon-aluminum gelling materials based on the optimal raw material dissolution characteristics of the present invention is feasible. Since the traditional orthogonal test method needs to design a large number of experimental studies as the basis for exploration, and it is necessary to determine the optimal formula by detecting the various properties of the silicon-aluminum gelling materials finally prepared, the time for determining the optimal formula is long, the efficiency is low, and a large amount of resources need to be consumed. Compared with the traditional orthogonal test method, the design method for determining the optimal ratio of raw materials for preparing silicon-aluminum gelling materials based on the optimal raw material dissolution characteristics adopted by the present invention can only be carried out by mixing the activator and the precursor in different proportions for ion dissolution, and selecting the optimal formula according to the optimal ion dissolution, omitting the steps of preparing silicon-aluminum gelling materials, curing them, detecting the performance, and screening out the optimal silicon-aluminum gelling materials to determine the optimal formula, which not only saves time, greatly improves efficiency, but also reduces investment costs.
[0235] In addition, the present invention adopts a design method for determining the optimal ratio of raw materials for preparing silicon-alumina gelling materials based on the optimal raw material dissolution characteristics, and can also judge the elements that need to be supplemented and added based on the dissolution rate of silicon, aluminum, and calcium in the ion dissolution process and the formation mechanism of silicon-alumina gelling materials, and then make appropriate proportion adjustments according to the richness of silicon, aluminum, and calcium contained in the precursor raw materials to improve the formula. Therefore, the design method for determining the optimal ratio of raw materials for preparing silicon-alumina gelling materials based on the optimal raw material dissolution characteristics proposed by the present invention is more flexible, which is more valuable for preparing silicon-alumina gelling materials using industrial solid waste as precursors, because the content of elements such as silicon, aluminum, and calcium in industrial solid waste is basically different, so the formula needs to be adjusted during the preparation process to adapt to the characteristics of the raw materials.
[0236] More importantly, the present invention also shows through the example study that in the process of preparing silicon-aluminum cementitious materials, the more activators are added, the better the ion dissolution is not; on the contrary, when the activator dosage is too much, it will lead to the deterioration of the performance of the silicon-aluminum cementitious materials. For example, when the activator dosage is too much, it will lead to increased shrinkage. This is because too much activator will accelerate the hydration reaction and affect the pore structure, thereby increasing its shrinkage characteristics. The occurrence of the above situation will be unfavorable to the development of the strength of the silicon-aluminum cementitious materials; in addition, too much activator dosage may also affect the durability performance indicators of concrete such as impermeability and freeze-thaw resistance, and reduce its service life; in addition, too much activator will reduce the fluidity of the mixture and increase the difficulty of construction; too much activator may also affect the setting time and hardening speed of concrete, resulting in an extension of the construction period or a decrease in construction quality. Relatively speaking, the traditional orthogonal test method cannot objectively and accurately judge whether the activator dosage is excessive, and because the orthogonal test is not a comprehensive test, the formula finally determined by the best silicon-aluminum cementitious material obtained may not be the best formula. Significantly different from the traditional methods, the design method provided by the present invention for determining the optimal ratio of raw materials for preparing silica-alumina gelling materials based on the optimal raw material dissolution characteristics can objectively and accurately control the dosage of the activator through the ion dissolution situation. This also solves the problem that the actual amount of activator used in the traditional silica-alumina gelling material preparation process far exceeds the demand for the solid waste to be activated, which in turn leads to problems such as alkali precipitation and durability of the silica-alumina gelling materials.
[0237] Based on the above, the design method for determining the optimal ratio of raw materials for preparing silica-alumina gelling materials based on the optimal raw material dissolution characteristics proposed by the present invention has practical value and economic value.
[0238] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0239] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for designing the proportion of a silicon-alumina gelling material, characterized in that: It includes the following steps: The precursor and the activator solution are mixed in different proportions for ion dissolution; the optimal ion dissolution rate judgment rule is as follows: the dissolution amount of silicon ions is X, the dissolution amount of aluminum ions is Y, and the dissolution amount of calcium ions is Z; the sum of aX and Y is the largest, and Y:X is 0.10-0.50:1; bX and Y have the largest ratio; cZ has the largest value; the priority of the optimal ion dissolution rate judgment is a>b>c; The proportion of silica-alumina gelling material is determined according to the optimal dissolution rate of ions.
2. The method for designing a ratio according to claim 1, characterized in that: The precursor is industrial solid waste.
3. The method according to claim 2, characterized in that The industrial solid waste is any one or more of metakaolin, red mud, mineral powder, steel slag, lithium slag, gypsum, coal gangue, fly ash, coal cinder, and blast furnace slag.
4. The method according to claim 3, characterized in that The activator is at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate and potassium sulfate.
5. The method according to claim 4, characterized in that The Y:X is 0.15-0.35:
1.
6. The method according to claim 3, characterized in that When the precursor contains two kinds of industrial solid wastes, the precursor is prepared by mixing the precursor with the activator solution in proportions of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, respectively.
7. The method according to claim 3, characterized in that When the precursor contains three kinds of industrial solid wastes, the precursor is prepared by mixing them in proportions of 6:2:2, 2:6:2, 2:2:6, 1:4.5:4.5, 1:2:7, and 1:7:2 before mixing the precursor with the activator solution.
8. The method according to claim 4, characterized in that During the mixing process of the precursor and the activator solution, the mass ratio of the activator dosage to the precursor is 1.0%, 3.0%, 5.0%, 7.0% and 9.0% based on the solid content.
9. The method according to claim 4, characterized in that It also includes the following steps: After the precursor and activator solutions are mixed, the resulting mixture is cooled to room temperature before ion dissolution begins.
10. The method according to claim 9, characterized in that The dissolution test temperature for the ion dissolution is 20-25°C; the dissolution time is 60-80 minutes.
11. The method according to claim 9 or 10, characterized in that: The method further comprises the following steps: during the ion dissolution process, the mixed solution is stirred at a stirring speed of 800 to 1200 rpm.
12. A silicon-alumina gelling material, characterized in that: The mortar formed has a flexural strength of >6.0MP and a compressive strength of >40.0MP after being cured in water for 3 days; and a flexural strength of >7.0MP and a compressive strength of >41.0MP after being cured in water for 28 days.
13. Use of the silicon-aluminum gelling material as claimed in claim 12 in the fields of building decoration, road traffic engineering, building foundation, floor or roofing materials.